Impacto de los OGM en la productividad agrícola y la seguridad alimentaria - Bajaña Bravo, Patricio Enrique (2024)
Agriculture plays a crucial role in human survival, the economy and environmental preservation. It is essential to combat extreme poverty, promote collective prosperity and ensure food for an estimated 10 billion people. In Ecuador, agriculture provides employment, food and raw materials, and contributes 8.5% of GDP and 25% of the working population. This work aims to analyze the impact of GMOs on agricultural productivity and food security. The methodology used was non-experimental bibliographic research. This work was developed as non-experimental bibliographic research using the analysis technique, journals, current texts, articles synthesis and summary of the data collected. Regarding the results, Genetically Modified Organisms represent a substantial impact on the contribution, availability and accessibility of safe and nutritious food, therefore, farmers grow a greater amount of food on a smaller area of land, thus meeting the growing demand of the world population. Due to their resistance to pests, diseases and adverse environmental conditions, genetically modified organisms (GMOs) improve crop yields, reduce post-harvest losses and improve nutritional quality. While most studies indicate that GMOs are safe for consumption, ongoing research to ensure long-term safety remains necessary, emphasizing the importance of careful research in this field.